Implementing psychological support for health and social care staff affected by the COVID-19 pandemic: a qualitative exploration of staff well-being hubs (‘Resilience Hubs’) using normalisation process theory - Daniel Hind; Kate Allsopp; Alan Barrett; Paul French; Filippo Varese; Hannah White; Priscilla Chung; Alysha A Hassan; Sally-Anne Wright; Ellie Young; Gita Bhutani; Katherine McGuirk; et al. (BMJ Open)
Objectives Evaluate the implementation of Hubs providing access to psychological support for health and social care keyworkers affected by the COVID-19 pandemic.Design Qualitative interviews informed by normalisation process theory to understand how the Hub model became embedded into normal practice, and factors that disrupted normalisation of this approach.Setting Three Resilience Hubs in the North of England.Participants Hub staff, keyworkers who accessed Hub support (Hub clients), keyworkers who had not accessed a Hub, and wider stakeholders involved in the provision of staff support within the health and care system (N=63).Results Hubs were generally seen as an effective way of supporting keyworkers, and Hub clients typically described very positive experiences. Flexibility and adaptability to local needs were strongly valued. Keyworkers accessed support when they understood the offer, valuing a confidential service that was separate from their organisation. Confusion about how Hubs differed from other support prevented some from enrolling. Beliefs about job roles, unsupportive managers, negative workplace cultures and systemic issues prevented keyworkers from valuing mental health support. Lack of support from managers discouraged keyworker engagement with Hubs. Black, Asian and minority ethnic keyworkers impacted by racism felt that the Hubs did not always meet their needs.Conclusions Hubs were seen as a valuable, responsive and distinct part of the health and care system. Findings highlight the importance of improving promotion and accessibility of Hubs, and continuation of confidential Hub support. Policy implications for the wider health and care sector include the central importance of genuine promotion of and value placed on mental health support by health and social care management, and the creation of psychologically safe work environments. Diversity and cultural competency training is needed to better reach under-represented communities. Findings are consistent with the international literature, therefore, likely to have applicability outside of the current context.